Pharmacological and Toxicological Study of Coumarinolignoids from Cleome viscosa in Small Animals for the Management of Rheumatoid Arthritis - Babu, Vineet; Singh, Rupali; Kashyap, Praveen K.; Washimkar, Kaveri R.; Mugale, Madhav N.; Tandon, Sudeep; Bawankule, Dnyaneshwar Umrao (Planta Medica, 2022)
This study aims to explore the possible pharmacological potential of Cleome viscosa Linn (Cleomaceae), an annual weed, into therapeutic value-added products. In the present study, we have explored the pharmacological and toxicological profile of coumarinolignoids isolated from Cleome viscose for the management of rheumatoid arthritis and related complications in a small animal model. To avoid the biasness during experiments on animals, we have coded the isolated coumarinolignoids as CLIV-92 to perform the experimental pharmacological study. CLIV-92 was orally administrated (30,100, 300 mg/kg) to animal models of collagen-induced arthritis (CIA), carrageenan-induced acute inflammation, thermal and chemical-induced pain, and Brewerʼs yeast-induced pyrexia. Oral administration of CLIV-92 significantly decreases the arthritis index, arthritis score, and increases the limb withdrawal threshold in the CIA model in experimental rats. The anti-arthritis studies revealed that the anti-inflammatory effect of CLIV-92 was associated with inhibition of the production of inflammatory mediators like TNF-α, IL-6, IL-17A, MMP-1, MMP-9, Nitric oxide, and C-RP in CIA ratʼs serum, and also reduced the NFкB-p65 expression as evidence of immunohistochemistry in knee joint tissue of CIA rats, in a dose-dependent manner. Further individual experiments related to arthritis-related complications in experimental animals demonstrated the analgesic, anti-inflammatory, and antipyretic potential of CLIV-92 in a dose-dependent manner. Further, an in-vivo acute oral toxicity study concluded that CLIV-92 is safe in experimental animals up to 2,000 mg/kg dose. The results of this study suggested that the oral administration of CLIV-92 may be a therapeutic candidate for further investigation in the management of rheumatoid arthritis and related complications.
Keywords: Coumarinolignoid; Cleome viscosa; Cleomaceae; rheumatoid arthritis; experimental animals